Regulating The Waiting Period For The Execution Of Capital Punishment: A Legal Certainty And Prisoners' Rights Protection Perspective After The Enactment Of Law Number 1 Of 2023 On The Criminal Code - Ceria Sitepu; Faizin Sulistio; I Nyoman Nurjaya (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Indonesia's newly enacted Criminal Code, Law Number 1 of 2023, reclassifies capital punishment from a primary penalty into a special and conditional sanction accompanied by a ten-year probationary period. This reform was intended to reconcile the death penalty with contemporary principles of humanity and rehabilitation. However, neither the new Code nor its predecessor regulation establishes a definite time limit within which an execution must be carried out following the exhaustion of legal remedies or the expiry of the probationary period. Empirical evidence shows that numerous death-row convicts in Indonesia have endured waiting periods far exceeding the maximum term of fixed-term imprisonment, in some cases spanning more than two decades, exposing them to what may be characterized as a double punishment and prolonged psychological uncertainty. Employing normative legal research through statutory and conceptual approaches, this article examines the regulatory vacuum surrounding the waiting period for execution under Indonesian law and evaluates its implications for the principle of legal certainty and the protection of convicts' fundamental rights. Drawing on Gustav Radbruch's theory of legal certainty and Lon Fuller's principles of the inner morality of law, the study argues that the absence of a clearly promulgated and consistently applied time frame undermines both the normative coherence of the criminal justice system and the constitutional guarantee of legal certainty. The article concludes by underscoring the urgency of further statutory regulation to close this normative gap and to safeguard the rights of death-row convicts pending execution.